MASALAH DEFINISI PEMBAGIAN DI KELOMPOK MASYARAKAT DESA DOLOK MANAMPANG, KECAMATAN DOLOK MASIHUL, KABUPATEN SERDANG BEDAGAI - Indryansa, Afiva; Harahap, Indra (Yayasan Amanah Nur Aman, 2025)
This study discusses the problematics of splinter groups (splinter sects) that have emerged in Dolok Manampang Village and their impact on the religious and social life of the local community. This phenomenon has drawn attention due to the emergence of teachings that deviate from mainstream Islam, both theologically and in ritual practices. The research focuses on several key aspects: the identity and doctrinal deviations of the splinter group, the resulting social and religious impacts, the responses of the community and religious leaders, and efforts to strengthen faith and maintain social harmony. The research employs a descriptive qualitative approach using data collection techniques such as interviews, observation, and document analysis. The findings show that the presence of the splinter group has caused unrest among residents, leading to disrupted social harmony and polarization in community relations. Religious leaders and community members have responded with various approaches, including rejection, religious education, and open dialogue to prevent further conflict. Comprehensive strategies are needed to counter the negative influence of such groups, including strengthening faith-based education within the community, inclusive religious counseling, and collaboration among religious leaders, educational institutions, and village authorities. These efforts aim to preserve social cohesion, reinforce religious conviction, and prevent social disintegration caused by extreme ideological differences.